SMKN 1 DLANGGU's STRATEGY IN DEFELOPING STUDENTS INTEREST IN INDONESIAN TRADITIONAL ARTS AMIDST THE INFLUENCE OF THE KOREAN WAVE - Amanda Putri Violita (Universitas Negeri Surabaya, 2026)
This study aims to describe the resilience strategies employed by SMKN 1 Dlanggu to preserve Indonesian traditional arts in the era of the influx of foreign cultures, including the Korean Wave. It also describes how students maintain Indonesian traditional arts so they can compete with the proliferation of foreign cultures. This study uses a qualitative descriptive approach with the aim of analyzing resilience strategies at SMKN 1 Dlanggu. This approach begins with collecting, processing, and presenting data objectively to address the problem formulation. The data sources used were primary and secondary data sources. Data collection techniques used in this study included observation, interviews, documentation, and questionnaires. The collected data were then analyzed through three stages: data reduction, data presentation, conclusion drawing, and verification. The analyzed data were then validated using several data checks, research results show that the majority of students at SMKN 1 Dlanggu still maintain their love for Indonesian traditional arts despite the influx of foreign cultures. This demonstrates that SMKN 1 Dlanggu's strategy to preserve Indonesian including source triangulation and technique triangulation, to ensure data validity.The culture has been successful, and that students can develop Indonesian arts through the support provided by the school. Keywords: Korean Wave, Indonesian Tradisional Art, Survival Strategy